DADOS PETROLÓGICOS DOS DIABÁSIOS DOS SETORES CENTRO-NORTE E NORDESTE DO ENXAME DE DIQUES DA SERRA DO MAR - Corval, A.; Valente, S. C.; Duarte, B. P.; Famelli, N.; Zanon, M. (Geochimica Brasiliensis, 2012)